AlQalam Journal of Medical and Applied Sciences: Involvement and Recognition - Ahmed Atia1 and Nagib Elmarzugi2,3 (AlQalam Journal of Medical and Applied Sciences, 2020)
We are pleased to announce the reappearance of the AlQalam journal of medical and applied sciences (AJMAS) having been interrupted for one year and half, except for conference proceeding. The current issue will be the first online issue under the sponsorships of the University of Tripoli Alahlia (UTA), Janzur, Libya. Despite the uprising difficulties in Libya, we are delighted to re-construct the journal’s earlier track record funded by UTA. We assigned online International Standard Serial Number (eISSN: 2707-7179), an international Identifier for serials and other continuing resources, and also uploaded all previous issues and conference proceeding on the new webpage of the journal